Prolonged drought from winter to spring affected the phenology, growth, and physiology of differently pretreated Pinus sylvestris var. mongolica seedlings - Zheng, Fang; Qian, Hui; Liu, Yan; Ge, Yu-Lan; Di, Bao; Kilpeläinen, Jouni; Wang, Ai-Fang (Springer Nature, 2025)
Water availability at the beginning of the growth phase, and even before it, is decisive in the phenology and annual cycle of forest trees, consequently affecting carbon sequestration and forest ecosystem balance. This is a novel experimental study on the effects of continuous drought throughout winter and early spring on tree performance. Two groups of Pinus sylvestris var. mongolica seedlings were overwintered in a Chinese solar greenhouse (BIG seedlings) and a plastic tunnel (SMALL seedlings). The seedlings were subjected to continuing droughts from winter to an extra 0 (control), 15 (D15), 30 (D30) and 45 days without irrigation (D45) after soil thawing next spring. Bud phenology, tree growth and physiology were examined. Bud phenological development, tree aboveground growth and root biomass growth were delayed in treatments D30 and D45 in both seedling types. SMALL seedlings had earlier bud phenology and were less influenced by drought than BIG seedlings. The drought-induced changes in spring phenology were associated with higher ABA and lower GA3 concentrations of needles. The phenology and growth differences between the seedling types might relate to soluble sugar concentrations of roots, needle chlorophyll content, needle chlorophyll fluorescence and acclimated morphological changes, such as root-shoot ratio. We suggest that in forest management, a big seedling size does not guarantee growth success, but attention should be paid to the proper conditions in overwintering and storing of the seedlings prior planting. Prolonged drought throughout winter and early spring should be avoided especially before planting the seedlings in an area prone to drought.
Keywords: Mongolian Scots pine; aridity; bud phenology; nonstructural carbohydrates; endogenous hormones; seedling size